Increasing outcomes of the results learn through project based learning - Nizamuddin Nizamuddin; Samidjo Samidjo; Nurcholish Arifin Handoyono (Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of the research is to know the effectiveness of learning outcomes of light vehicle engine maintenance subjects between students who are following a project based learning models compared with students who are following learning with conventional models. The type of this research is Quasi-experimental with a population consist of 54 students and divided into two classes, namely XI TKR 1 and XI TKR 2. The samples were taken on a clustered basis and found XI TKR 2 class as an experimental class with 27 students and XI TKR 1 class as an control class consist of 27 students. The instrument of data collection is used multiple choice tests. The technique of data analysis using descriptive, the prerequisite test analysis using a normality test and homogeneity test, while the hypothesis is using t-test. The results of the study were the results of learning by implementing a project based learning models in the experimental class higher than applying conventional models in control class. This can be proved by testing the t-test in the post-test between the experiment and control class which shows the t-hitung > t-tabel value, (2,189 > 1,674) and its significance value is less than 0.05 (P = 0.02 < 0.05).